Effect of foliar spray with seaweed extract (Sprintal) and ascorbic acid on some growth and production indicators and quality of apple cv. Starking Delicious - ديب علي; صهيوني فهد; بلال عصام (Latakia University Journal -Biological Sciences Series, 2022)
The study was carried out at Blouta village of Al-Haffa city in Lattakia governorate, on trees of the Starking Delicious cultivar, total area of 5 dunums During the year 2019 on trees 20 years old and planted with (5*5) m spacing and grafted on Malus domestica Borkh rootstock. The experiment was designed in complete randomized way, and included four treatments with five replications and one trees in each replication: (1) control: Spray only with water, (2) Spray with algae extract Sprintal at concentration of 0.5 cm3/l (52.5 PPM N, 115 PPM Organic carbon), (3) Spray with ascorbic acid at concentration of 0.5 g / l, (4) Spray with algae extract Sprintal at concentration of 0.5 cm3/l (52.5 PPM N, 115 PPM Organic carbon) and Spraying with ascorbic acid at concentration of 0.5 g / l. Foliar spraying with ascorbic acid at concentration of 0.5 g/l and algae extract at concentration of 0.5 cm3/l, alone or in combination improved the studied characteristics. The treatment of foliar spraying with ascorbic acid at concentration of 0.5 g/l and algae extract at concentration of 0.5 cm3/l together gave the best results, as it increased the size of the crown (79)% and percentage of contract (22.70)% and production (54.48)kg/tree compared to the control )41.62(% و) 18.09( % و) 34.55) kg/tree respectively, and it gave the largest weight and volume of the fruit (172.9)g, (187.4)cm3 compared to the control (143.2)g and (156.2)cm3 respectively, and increased the percentage of total soluble solids and total sugars (15.04)%and (12.92)% compared to the control (13.46)%and (11.48)%